Intersectionality of race and gender in practice: black women's movements at international conferences - Ferreira, Sibelle de Jesus (2023)
This work presents the context of the participation of black Brazilian women in UN international conferences, with emphasis on the Beijing Conference in 1995 and the Durban Conference in 2002. In order to demonstrate the development of black women's movements in this period, it seeks to reflect on how the premise of the intersectionality of gender and race as basic values of their activist action was crucial for the transnational articulation achieved, which enabled the advancement of policies in favor of racial equality in Brazil. The focus on the experience and international trajectory of the black women's movement is based on a historical analysis, highlighting the main events and achievements made based on the existing bibliographic records.